2018
DOI: 10.3389/feart.2018.00003
|View full text |Cite
|
Sign up to set email alerts
|

Weak Tectono-Magmatic Relationships along an Obliquely Convergent Plate Boundary: Sumatra, Indonesia

Abstract: The tectono-magmatic relationships along obliquely convergent plate boundaries, where strain partitioning promotes strike-slip structures along the volcanic arc, are poorly known. Here it is unclear if and, in case, how the strike-slip structures control volcanic processes, distribution and size. To better define the possible tectono-magmatic relationships along strike-slip arcs, we merge available information on the case study of Sumatra (Indonesia) with field structural data. The Sumatra arc (entire volcanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 101 publications
(177 reference statements)
0
36
0
1
Order By: Relevance
“…This is in line with the Global Positioning System (GPS) data studied by McCaffrey et al (2000) that suggested a uniform slip rate of 21 ± 5 mm yr −1 across central Sumatra. A geomorphology study of the SFZ by Sieh and Natawidjaja (2000) and Acocella et al (2018) found it to be highly segmented with 19 major geometrically defined segments. Termed "equatorial bifurcation", the largest irregularity is located at the Equator, where the fault separates into two subparallel branches at approximately 35 km apart (Sieh and Natawidjaja, 2000).…”
Section: Interplate Faults In the Sumatran Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with the Global Positioning System (GPS) data studied by McCaffrey et al (2000) that suggested a uniform slip rate of 21 ± 5 mm yr −1 across central Sumatra. A geomorphology study of the SFZ by Sieh and Natawidjaja (2000) and Acocella et al (2018) found it to be highly segmented with 19 major geometrically defined segments. Termed "equatorial bifurcation", the largest irregularity is located at the Equator, where the fault separates into two subparallel branches at approximately 35 km apart (Sieh and Natawidjaja, 2000).…”
Section: Interplate Faults In the Sumatran Regionmentioning
confidence: 99%
“…Although numerous GMPEs have been developed and applied worldwide, not many GMPEs are available exclusively for Peninsular Malaysia due to its relatively lower local seismicity and distant location from active seismic hotspots such as the Sumatran region. Naturally, past attempts either adapted or adopted regional GMPEs or relied on the available limited data for developing GMPEs suitable for this region (Adnan et al, 2005;Pan and Megawati, 2002;Petersen et al, 2004). The collection of seismic ground motion data since 2004 by MMD, albeit relatively smaller in quantity compared to more earthquake active regions, has since allowed researchers to either identify suitable GMPEs (Van et al, 2016) or develop independent GMPEs for the peninsula (Adnan and Suhaltril, 2009;Loi, 2018;Nabilah and Balendra, 2012;Shoushtari et al, 2016) using the available ground motion records.…”
Section: Ground Motion Prediction Equations (Gmpes)mentioning
confidence: 99%
See 1 more Smart Citation
“…In the second case, volcanic activity may be partly controlled by the regional tectonic activity, including the seismic cycle of the subduction zone (Acocella, , and references therein). In particular, the latter feature has been object of several recent studies (Acocella et al, ; Eggert & Walter, ; Hill et al, ; Manga & Brodsky, ; Pritchard et al, ; Takada & Fukushima, ; Walter & Amelung, ). The consensus is that the activity of faults and the related seismicity along the subducting and the overriding plates may be responsible for extension in the overriding plate, from the trench to the area of the volcanic arc included.…”
Section: Introductionmentioning
confidence: 97%
“…This is in line with the Global Positioning System (GPS) data studied by McCaffrey et al (2000) that suggested a uniform slip rate of 21 ± 5mm/year across central Sumatra. A geomorphology study on the SFZ by Sieh and Natawidjaja (2000) and Acocella et al (2018), found that it is highly segmented and can be divided into 19 major geometrically defined segments. Termed "equatorial bifurcation', the largest irregularity is located at the equator, where the fault separates into two subparellel branches at approximately 35 km apart (Sieh and Natawidjaja, 2000).…”
mentioning
confidence: 99%